Humanist Education: Its Implementation on Scavengers Children’s at TPA Mancani Palopo City - Erwatul Efendi; Nurdin K; Baderiah Baderiah (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This study aims to determine the models and constraints of humanistic education carried out by educators for the child scavengers in the garbage dumps in Palopo City. This research is qualitative research for disclosing facts—Miles and Huberman's analysis using data collection, data reduction, data presentation, and conclusion. The results showed that: Education of scavenger children at TPA Mancani, Palopo City is more directed to public and religious educational institutions outside the garbage dumps area, educational guidance on Sundays at church for those who are Christian while those who are Muslim get an education at the Al-Qur'an Education Park (TPQ); humanist education is developing in Sunday schools with the concept of primary religious education, regular discussions, counseling, the formation of work and study groups with materials consisting of: beliefs, politeness/ethics, and memorizing verses. The methods used include: exemplary and discipline, habituation, advice and guidance, deliberation and discussion, stories or stories, as well as balancing the giving of praise and punishment; The obstacles faced in implementing humanist education for child scavengers at TPA Mancani Palopo City include; the recruitment as fostered children in Sunday School, the lack of support from parents, child scavengers feel that their freedom is losing after entering school, and not guarantee their worthiness of life. Another obstacle is the limited number of assistants of child scavengers, limited facilities, infrastructure, funds, and the character traits of scavenger children that are difficult to change.